Effectiveness of virtual reality-based vestibular rehabilitation in patients with peripheral vestibular hypofunction - Başoğlu, Yuşa; Şerbetçioğlu, Mustafa Bülent; Çelik, İlayda; Demirhan, Hasan (Turkiye Klinikleri, 2022)
Indexed keywords Metrics Abstract Background/aim: The rehabilitation of classical peripheral vestibular disorders is long and costly. Recently, interactive systems based on virtual reality (VR) technology have reduced the cost of vestibular rehabilitation therapy (VRT) and made the process more enjoyable. This study aims to investigate the effects of VR-based VRT in patients diagnosed with peripheral vestibular hypofunction (PVH). Materials and methods: In this study, a VR-based VRT program that utilized Sony Playstation®4 VR Head Mounted Display was applied to 25 patients (between 18–60) diagnosed with PVH. PVH was diagnosed by evaluating the patients’ clinical histories, the findings in the “Micromedical Technologies VisualEyes Spectrum” videonystagmography (VNG) and the “Micromedical Aqua Stim” model bithermal water caloric tests. VR-based VRT program was applied to the patients for 4 weeks, 2 sessions per week, 8 sessions in total. Each session lasted around 30 to 40 min. All patients underwent the Dizziness Handicap Inventory (DHI), Sensory Organization Test (SOT), Adaptation Test (ADT), Limits of Stability (LOS), and Rhythmic Weight Shift (RWS) before, after, and 8-week follow-up of the VRT program. In addition, the Cybersickness Survey was applied to the patients at the end of the VR-based VRT session every week. Results: The DHI mean scores of the patients were 54.60, 19.20, and 16.84, respectively, before, just after, and at the 8-week follow-up VRT (p < 0.001). The mean SOT composite score of the patients was obtained as 58.08 before VRT; 77.16 after VRT and 76.40 at 8-week after VRT (p < 0.000). On the other hand, the values in the ‘movement velocity’ and “direction control” parameters of the patients in LOS and RWS showed a significant improvement after VRT compared to before VRT (p < 0.000). From before VRT to 8 weeks after VRT, the patient’s oscillation averages in the ‘toes up’ and ‘toes down’ positions in ADT reduced progressively (p < 0.000). Conclusion: This study demonstrates that implementing a VR-based VRT protocol may be an efficient option to improve posture stability and the quality of life in patients with PVH. In addition, VR-based vestibular rehabilitation therapy has shown to be effective for PVH patients in the mid-term.
Keywords: Vestibular Rehabilitation Therapy; Virtual Reality; Vestibular Hypofunction